2019
DOI: 10.5812/hmj.91436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic Training and C. vulgaris Intake on Lipid Profile and Leptin in Obese Women

Abstract: Background: Regular physical activity can reduce the complications of obesity. Chlorella vulgaris (C. vulgaris) is recognized as a rich source of health promotion. Objectives: The aim of this study was to evaluate the effect of aerobic training and C. vulgaris intake on lipid profile and leptin in obese women. Methods: We randomly divided 32 obese women into control (C), aerobic training (AT), C. vulgaris (CV), and aerobic training plus C. vulgaris (AT+CV) groups. Interventions were performed for eight weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Resistance training did not decrease BMI or fat mass in our study of obese males, a finding that could explain the lack of leptin reduction by resistance training. Other studies reported that CV did not mitigate increases in leptin levels in obese mice ( Vecina et al, 2014 ) and obese women ( Karbalamahdi et al, 2019 ). However, a study of patients with T2DM and prediabetes patients reported that the CV intake for 12 months decreased plasma leptin levels ( Martins et al, 2023 ), while another study reported decreases in leptin levels in obese mice treated with Parachlorella beijerinckii , an algae that is also used as a food supplement ( Noguchi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
“…Resistance training did not decrease BMI or fat mass in our study of obese males, a finding that could explain the lack of leptin reduction by resistance training. Other studies reported that CV did not mitigate increases in leptin levels in obese mice ( Vecina et al, 2014 ) and obese women ( Karbalamahdi et al, 2019 ). However, a study of patients with T2DM and prediabetes patients reported that the CV intake for 12 months decreased plasma leptin levels ( Martins et al, 2023 ), while another study reported decreases in leptin levels in obese mice treated with Parachlorella beijerinckii , an algae that is also used as a food supplement ( Noguchi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 93%